2021
DOI: 10.1515/znb-2020-0204
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, cytotoxicity and in silico study of some novel benzocoumarin-chalcone-bearing aryl ester derivatives and benzocoumarin-derived arylamide analogs

Abstract: The development of new prostate cancer protein receptor cytochrome P450 17A1 inhibitors offers the possibility of generating structures of increased potency. To this end, the chalcone analogs 7 and 8 were prepared from treatment of methyl 3-oxo-3H-benzocoumarin-2-carboxylate (4) with aryl aldehydes. Treatment of 7 and 8 with three anti-inflammatory drugs, flurbiprofen, ketoprofen and ibuprofen, in the presence of POCl3/DMAP gave the ester analogs 9–12. Analogously, treatment of ethyl 3-oxo-3H-benzocoumarin-2-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…from the reaction of methyl 3-oxo-3H-benzocoumarin-2-carboxylate with aryl aldehyde [109]. The synthesis of several 2-benzylidene-1-indanone derivatives and the evaluation of their inhibitory activity on lipopolysaccharides-stimulated reactive oxygen species production in RAW 264.7 macrophages has been reported [110,111]. An SAR study disclosed that the presence of a hydroxy group in the C-5, C-6, or C-7 position of the indanone moiety is important for the inhibition of reactive oxygen species production in LPS-stimulated RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…from the reaction of methyl 3-oxo-3H-benzocoumarin-2-carboxylate with aryl aldehyde [109]. The synthesis of several 2-benzylidene-1-indanone derivatives and the evaluation of their inhibitory activity on lipopolysaccharides-stimulated reactive oxygen species production in RAW 264.7 macrophages has been reported [110,111]. An SAR study disclosed that the presence of a hydroxy group in the C-5, C-6, or C-7 position of the indanone moiety is important for the inhibition of reactive oxygen species production in LPS-stimulated RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the synthesized compounds against prostate carcinoma was tested, and the findings revealed that two of them were the most effective compounds among this group. As a result, these candidates appear to be the most attractive antiproliferative agents towards CYP450 dependent prostate carcinoma cells [97].…”
Section: Bioactivities Of Benzocoumarins and Their Analoguesmentioning
confidence: 99%
“…Hyperglycemia and insulin resistance are hallmarks of type 2 diabetes, which eventually lead to a slew of long-term health problems as the disease progresses. These problems include renal and hepatic failure, neurological, retinal, and cardiovascular diseases [1]. Controlling hyperglycemia via targeting the inhibition of enzymes in the carbohydrate hydrolysis process, like α-glucosidase and αamylase, is one of the most effective treatment approaches for type 2 diabetes which should be considered [2].…”
Section: Introductionmentioning
confidence: 99%
“…The antidiabetic and antioxidative properties have taken on importance among the examined activities. As a result, benzocoumarins could serve as the structural templates for promising antidiabetic and antioxidative entities [1,40]. This study aimed to prepare new coumarindisubstituted benzene conjugates.…”
Section: Introductionmentioning
confidence: 99%